Knowledge and Strategies of Controlling Plagiarism at the University of Dar es Salaam, Tanzania - Mbilinyi, Debora; Msuya, Jangawe (University of Dar es Salaam Library Journal, 2019)
This paper presents findings of a study conducted at the University of Dar es Salaam (UDSM) Tanzania concerning academic staff and students ' knowledge of plagiarism. The study investigated forms of plagiarism practiced and prevention strategies used. Questionnaires were used to collect data from students and academic staff. In contrast to academic staff, students were found to have insufficient knowledge on plagiarism despite the existence of various strategies for awareness creation on the problem. The results study has revealed various plagiarism forms practiced at the University, as well as prevention measures used. The study ends with a set of strategies to control plagiarism, in addition to e existing initiatives.